Enabling development : the impact on residential amenity : a survey of the experiences of affected parties under the RMA : a thesis presented in partial fulfilment of the requirements for the degree of Master of Resource and Environmental Planning at Massey University - Conning, Linda (Massey University, 2009)
The majority of resource consent applications for land use under New Zealand's Resource Management Act 1991 are not publicly notified. This enables development, through the efficient processing of applications considered to be of minor or localized effect. However written approvals may be required from all persons the consent authority considers adversely affected by such applications. If these approvals are not forthcoming, the application is then subject to "limited notification", and notified, if at all, only to affected parties. A study was undertaken to determine what influences people to give or withhold such written approval, and what were the outcomes for those people. The study sought to discover whether responses within the process mirror wider environmental issues. In 2008 a questionnaire was sent to a sample of affected parties in Tauranga and the Western Bay of Plenty, and in 2009, most of the respondents were subsequently interviewed. The theoretical framework behind the research is broad and ranges from the current planning context in New Zealand to the underlying philosophical concepts of the freedom of the individual and their rights, environmental justice, reasons and motivations behind planning disputes, including underlying psychological factors and the meaning of place. Whilst some responses were predictable, the extent of negative experiences was surprising, suggesting changes in both process and practice would lead to better outcomes for affected parties. Key Words: RMA, notification, planning process, affected parties, amenity, public interest, rights, justice, environmental attitudes, environmental behaviour.
Keywords: New Zealand. Resource Management Act 1991; New Zealand; Environmental policy -- Citizen participation; Environmental policy -- Public opinion; Regional planning -- Law and legislation